Effects of muscular strength training and growth hormone (GH) supplementation on femoral bone tissue: analysis by Raman spectroscopy, dual-energy X-ray absorptiometry, and mechanical resistance - Castoldi, Robson Chacon [UNESP]; Ozaki, Guilherme Akio Tamura; Garcia, Thiago Alves; Giometti, Ines Cristina; Koike, Tatiana Emy [UNESP]; Camargo, Regina Celi Trindade [UNESP]; dos Santos Pereira, João Domingos Augusto [UNESP]; Constantino, Carlos José Leopoldo [UNESP]; Louzada, Mário Jefferson Quirino [UNESP]; Camargo Filho, José Carlos Silva [UNESP]; Belangero, William Dias (Springer Nature, 2019)
The aim of the present study was to verify the effects of muscular strength training and growth hormone (GH) supplementation on femoral bone tissue by Raman spectroscopy (Raman), dual-energy X-ray absorptiometry (DXA), and mechanical resistance (F-max) analysis. A total of 40 male Wistar animals, 60 days old, were used. The animals were distributed into four groups: control (C), control with GH (GHC), muscular strength training (T), and muscular strength training with GH (GHT). Blood samples were collected for the quantification of creatine kinase (CK-MB) and the femurs were removed for analysis by Raman, DXA, and F-max. A more pronounced increase in the bone mineral components was verified in the T group, for all the variables obtained by the Raman (calcium, phosphate, amide, and collagen). In addition, for animals submitted to GH supplementation, there was a reduction in the variable bone mineral density (BMD) obtained by the DXA (p < 0.05). Finally, the animals that received GH supplementation presented a higher F-max, but without statistical significance (p > 0.05). It was concluded that animals that received GH supplementation demonstrated a decrease in BMD. In addition, T alone was able to promote increased calcium, phosphate, amide, and collagen compounds in bone tissue.
Keywords: Anabolics; Bone tissue; Growth hormone; Muscular strength; Physical training